A produção de texto narrativo escrito de alunos do 5º ano do Ensino Fundamental: do relato à história - Silva, Roseneide Simões da (2017)
This dissertation is linked to the research line: Text and Speech in oral and written format, the Program of Studies in Portuguese language of PUC-SP. It is therefore subject to present a proposal for a teaching of gender-textual narrative discourse of history for students of the 5th year of elementary education at a public school peripheral areas of the city of São Paulo.The problem addressed in this research is to find out what strategies are applied to the construction of the narrative genre of history. It is a general objective to contribute to the teaching proposal of the genre textual-discursive narrative of history. Specific objectives are: Diagnose what the student already knows about the production of written text of the narrative genre of history; To propose a didactic sequence that propitiates an improvement in the written production of the textual genre: history narrative; Apply activities of production of written text of the narrative genre of history; It is general objective contribute with the proposal of teaching of gender textual-discursive narrative of history. Are specific objectives: to diagnose what students already know about the production of written text of the narrative genre of history; Propose a didactic sequence that drives an improvement in written production of textual genre: narrative of history; apply the production of written text of the narrative genre of history; To verify the use of textual categories (presentation, conflict, resolution, followed by evaluation or morality) in the production of written text of the narrative textual genre of history.The methodological procedure is qualitative analytical with application of a didactic sequence in the classroom. The analysis material was collected from students-informants of the 5th year. The results obtained indicate that the proposal made in this dissertation, permitted them to differentiate into narrative report of narrative of history; as well as produce texts of the narrative of history as well organized. We conclude that the proposed strategies are effective and that teachers, in general, have difficulties to teach the difference between narrative account of the narrative of history, because they have little theoretical knowledge of the subject treated